Os impactos sobre a biodiversidade e saúde humana decorrentes da utilização de agrotóxicos no Brasil - Carvalho, Gleizeane Santos Almeida de (2017)
The present dissertation realyze a analyze about the resulting impacts on biodiversity and human from the use of pesticides in Brazil. In this context, we initially present about the insertion of pesticides in Brazilian agribusiness. However, to substantiate this insertion it was necessary to explain the roots of the International Division of Labor - IDL, demonstraionsting how the impositions coming from this IDL affects on the course taken by capitalism in Brazil. In this way, it was essential to display the historical-critical assumptions about the emergence of inequality and class society. We elucidate how this articulation of capitalist society justifies the theory of the uneven and combined development of capitalism. Thus, we explain the supports that propitiate the understanding of the genesis of the Brazilian economic formation, with an agrarian capitalism exporter subservient to the impositions of international capital. In the process of development of capitalist society concomitant with the need to expansion of profits and the market, we find in the Green Revolution the capitalist alternative to prevent the fall in the rate of profit post crisis period of capitalist society. In this wake, it was necessary to show how in this process the doors were opened for the creation and commercialization of pesticides. Continuing the analysis we show how the use of these pesticides is occurs in the primary sector and we expose their functionality to the capital. In this way, we clarify which are the main companies foment this heinous market and what impacts come from the uncontrolled consumption of these agricultural poisons. In the end, we show the alternative of confrontation we have to fight against the harms caused by this problem caused by the use of these pesticides in Brazil.